THE LANGUAGE DELIVERY MASTERY IN MUHAMMAD ZAINI ABDUL GHANI TEACHING - Mahfud Afandi; Abdul hakim; Abdul Sani; Ahda Fithriani (Universitas PGRI Palembang, 2025)
Muhammad Zaini Abdul Ghani is a renowned religious scholar in South Kalimantan, recognized for his profound theological knowledge and ability to convey monotheistic teachings in an accessible manner. Rooted in the Ahlussunnah Wal Jama'ah tradition, his approach aligns with al-Sanusi’s scholarship and the Sifat Twenty teachings of Utsman bin Abdullah. This study explores his theological contributions and their impact on religious education and communal unity. Using a qualitative method, including textual analysis and historical research, the findings highlight his ability to bridge theoretical monotheism with practical application, fostering a strong faith and social harmony. His emphasis on moderation and unity reinforces Islamic values and strengthens community bonds. The study concludes that his teachings provide a balanced and practical approach to Islamic theology. Future research should compare his theological perspectives with other scholars and analyze their relevance in contemporary Islamic discourse.